A perspective on the use of polyphenols nano-formulation as a nutritional strategy to manage the symptoms of the infected patient with COVID-19 (Research, Society and Development, 2021)
Coronaviruses disease (COVID-19) vaccines have emerged worldwide to control this illness, albeit they cannot guarantee full effectiveness. Polyphenols possess antioxidant, anti-inflammatory, and antiviral properties, all of which may be effective against COVID-19 symptoms. Since polyphenols exhibit low bioavailability, polyphenols nano-formulation (a food technology) have been utilized in COVID-19 patients. Therefore, the purpose of this review is to discuss the current evidence showing the effects of polyphenols nano-formulation in COVID-19 patients. Two previous studies have demonstrated that polyphenols nano-formulation (particularly curcumin) can alleviate clinical manifestation (fever, tachypnea, myalgia, cough) and improve overall recovery since polyphenols can modulate the inflammatory response, oxidative stress, and upregulate certain proteins involved in the renin-angiotensin system, all which play a crucial role on the symptoms caused by COVID-19.